Effects of Ultrasound-Guided Acupotomy Therapy on a Trigger Finger: A Case Report - Ho Seok Jung; Tae Seong Jeong; Sung Chul Kim; Yeong Jin Jeong; Su Hak Kim; Jinwoong Lim (Journal of Acupuncture Research, 2023)
This study aimed to demonstrate a safe and effective procedure targeting the A1 pulley with ultrasound-guided acupotomy in patients with a trigger finger. Six ultrasound-guided acupotomy procedures were performed on 1 patient. The Numerical Rating Scale (NRS) score, Quinnell’s classification of triggering, Tanaka score, and A1 pulley thickness were measured using ultrasonography before and after treatment. This study revealed reduced NRS score, Quinnell’s classification of triggering, Tanaka score, and thickness of the A1 pulley, with no side effects during the procedure. This indicates ultrasound-guided acupotomy as an effective and safe treatment method for patients with a trigger finger. Further studies are required to evaluate the beneficial effects of this treatment.